Injectable Photo-Crosslinked Bioactive BMSCs-BMP2-GelMA Scaffolds for Bone Defect Repair - Chai, Senlin; Huang, Jianhao; Mahmut, Abdurahman; Wang, Bin; Yao, Yao; Zhang, Xiaofeng; Zhuang, Zaikai; Xie, Chunmei; Xu, Zhihong; Jiang, Qing (Frontiers in Bioengineering and Biotechnology, 2022)
Injectable hydrogels offer a new therapy option for irregular bone deformities. Based on gelatin methacryloyl (GelMA), bone marrow mesenchymal stem cells (BMSCs), and bone morphogenetic protein 2 (BMP2), we created a photo-crosslinked composite bioactive scaffold. The composite scaffolds had appropriate mechanical properties for stem cells adhesion and proliferation, as well as good biocompatibility and the ability to stimulate BMSCs osteogenic differentiation in vitro. The synergistic effect of BMSCs and BMP2 enabled the composite bioactive scaffold to exhibit higher osteogenic potential in vivo than scaffolds loaded alone with BMSCs or BMP2, according to imaging and histology studies. In conclusion, by promoting the osteogenic differentiation of BMSCs, the composite bioactive scaffold based on BMSCs-BMP2-GelMA has demonstrated remarkable application potential in bone regeneration and bone defects repair.